Modification of Chitosan-Coated Magnetic Material with Glycidyl-trimethylammonium Chloride for Cr(VI) Adsorption - Kamilia, Salwa; Mukhayani, Feri; Sutarno, Sutarno; Nuryono, Nuryono (Indonesian Journal of Chemistry, 2025)
Modification of chitosan-coated magnetic material with quaternary ammonium chloride as adsorbent for Cr(VI) anions has been studied. The works included magnetic material (MM) separation from iron sand, magnetic material-chitosan (MM/Chit) synthesis, and attachment of quaternary ammonium groups from glycidyl trimethyl ammonium chloride (GTMAC) on MM/Chit to produce MM/Chit/GTMAC with various mass ratios. Products were characterized with FTIR, XRD, SEM-EDX, and VSM. Adsorption studies were carried out in a batch system with pH, time, and initial Cr(VI) concentration variations. The unadsorbed Cr(VI) was analyzed with AAS, and the adsorbed Cr(VI) was calculated from the difference between initial and unadsorbed concentrations of Cr(VI). The results showed that MM/Chit/GTMAC was successfully synthesized, and adding GTMAC increased the stability of MM/Chit and shifted the optimum pH for Cr(VI) adsorption from 3.0 to 4.0. The study of kinetics and adsorption isotherm showed that the adsorption of Cr(VI) anion on the adsorbent MM/Chit/GTMAC (with the mass ratio of Chit to GTMAC 1:6) follows the pseudo-second-order kinetic model with the adsorption rate constant of 5.3 × 10−3 g mg−1 min−1 and Langmuir isotherms with the adsorption maximum capacity of 104.17 mg g−1, which has a potential to be applied for removing Cr(VI) from polluted wastewater.